CDK11 Loss Induces Cell Cycle Dysfunction and Death of BRAF and NRAS Melanoma Cells - Rehana L. Ahmed; Daniel P. Shaughnessy; Todd P. Knutson; Rachel I. Vogel; Khalil Ahmed; Betsy T. Kren; Janeen H. Trembley (MDPI AG, 2019)
Cyclin dependent kinase 11 (CDK11) is a protein kinase that regulates RNA transcription, pre-mRNA splicing, mitosis, and cell death. Targeting of CDK11 expression levels is effective in the experimental treatment of breast and other cancers, but these data are lacking in melanoma. To understand CDK11 function in melanoma, we evaluated protein and RNA levels of CDK11, Cyclin L1 and Cyclin L2 in benign melanocytes and BRAF- as well as NRAS-mutant melanoma cell lines. We investigated the effectiveness of reducing expression of this survival kinase using RNA interference on viability, clonal survival, and tumorsphere formation in melanoma cell lines. We examined the impact of CDK11 loss in BRAF-mutant melanoma on more than 700 genes important in cancer signaling pathways. Follow-up analysis evaluated how CDK11 loss alters cell cycle function in BRAF- and NRAS-mutant melanoma cells. We present data on CDK11, CCNL1 and CCNL2 mRNA expression in melanoma patients, including prognosis for survival. In sum, we found that CDK11 is necessary for melanoma cell survival, and a major impact of CDK11 loss in melanoma is to cause disruption of the cell cycle distribution with accumulation of G1- and loss of G2/M-phase cancer cells.